2016
DOI: 10.3171/2016.5.focus16168
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-day readmission and reoperation after surgery for spinal tumors: a National Surgical Quality Improvement Program analysis

Abstract: OBJECTIVE The goal of this study was to use a large national registry to evaluate the 30-day cumulative incidence and predictors of adverse events, readmissions, and reoperations after surgery for primary and secondary spinal tumors. METHODS Data from adult patients who underwent surgery for spinal tumors (2011–2014) were extracted from the prospective National Surgical Quality Improvement Program (NSQIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 103 publications
6
62
2
1
Order By: Relevance
“…However, patients with a history of COPD or hypertension and those at ASA Class IV were at higher risk of readmission, which supports the hypothesis of a sicker population and has also been found in previous investigations. 18,30 Future research specifically into shortterm outcomes of ACDF and CDR might further corroborate or challenge these findings.…”
Section: Discussionmentioning
confidence: 70%
“…However, patients with a history of COPD or hypertension and those at ASA Class IV were at higher risk of readmission, which supports the hypothesis of a sicker population and has also been found in previous investigations. 18,30 Future research specifically into shortterm outcomes of ACDF and CDR might further corroborate or challenge these findings.…”
Section: Discussionmentioning
confidence: 70%
“…is is 25fold higher than the thirty-day mortality rate of 0.04% for all pediatric orthopedic procedures reported to NSQIP-P in 2012 [26]. However, it is lower than the 3.3% mortality rate of adults undergoing spinal tumor resections in the adult NSQIP database between 2011 and 2014 [22]. Additionally, in our previous NSQIP study of adult bone and soft tissue sarcomas of the extremities, we found a thirty-day mortality rate of 0.4% [25].…”
Section: Sarcomamentioning
confidence: 73%
“…e adult registry is well established with over six hundred participating sites across the United States and a current case volume of 6,638,405 procedures performed between 2005 and 2017. NSQIP has been used to characterize patient characteristics and outcomes after surgical management of primary and metastatic tumors of the spine [22,23]. Our research team has also used NSQIP to study outcomes after surgical management of primary bone and soft tissue sarcomas and metastatic bone tumors of the extremities [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…e data collection and quality control methodologies for NSQIP have been previously described and shown to be reliable [15,16]. NSQIP has been used to characterize demographics, comorbidities, and early postoperative complications for primary and metastatic bone tumors of the spine [17,18] as well as retroperitoneal sarcomas [19]. Additionally, our research team has used NSQIP to evaluate outcomes after surgical management of metastatic tumors of the extremities.…”
Section: Introductionmentioning
confidence: 99%